2007
DOI: 10.1603/0046-225x(2007)36[910:eomaae]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Maternal Age and Environment on Offspring Vital Rates in the Oleander Aphid (Hemiptera: Aphididae)

Abstract: Maternal effects have the potential to affect population dynamics and evolution. To affect population dynamics, maternal effects must influence offspring vital rates (birth, death, or movement). Here, we explore the magnitude of nongenetic maternal influence on the vital rates of an insect herbivore and explore predictability of maternal effects with reference to published studies. We experimentally studied the effects of maternal age, host plant species (two Asclepias spp.), and density on offspring vital rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 72 publications
1
24
0
Order By: Relevance
“…Milkweed plants exhibit marked variation in the types, concentrations and toxicity of cardenolides they characteristically produce and also vary in other physiological traits and chemical defences such as trichomes, latex and phenolics (Agrawal, Fishbein et al., ; Rasmann & Agrawal, ). Some studies have demonstrated no effect of cardenolides on A. nerii survival, fecundity, development, density and growth rate, but these studies focused on low‐toxicity plant species or experimental applications to vary cardenolide production within a species (Mooney, Jones, & Agrawal, ; Mooney et al., ; Zehnder, Parris, & Hunter, ). Comparing milkweed species that vary more substantially in cardenolide toxicity, we found that host plants with increased and more nonpolar cardenolides have negative effects on A. nerii development and fecundity, consistent with other studies that have demonstrated that plant species characterized by more toxic cardenolides are negatively associated with A. nerii population growth (Agrawal, ; Colvin, Snyder, & Thacker, ; de Roode et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Milkweed plants exhibit marked variation in the types, concentrations and toxicity of cardenolides they characteristically produce and also vary in other physiological traits and chemical defences such as trichomes, latex and phenolics (Agrawal, Fishbein et al., ; Rasmann & Agrawal, ). Some studies have demonstrated no effect of cardenolides on A. nerii survival, fecundity, development, density and growth rate, but these studies focused on low‐toxicity plant species or experimental applications to vary cardenolide production within a species (Mooney, Jones, & Agrawal, ; Mooney et al., ; Zehnder, Parris, & Hunter, ). Comparing milkweed species that vary more substantially in cardenolide toxicity, we found that host plants with increased and more nonpolar cardenolides have negative effects on A. nerii development and fecundity, consistent with other studies that have demonstrated that plant species characterized by more toxic cardenolides are negatively associated with A. nerii population growth (Agrawal, ; Colvin, Snyder, & Thacker, ; de Roode et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, older mothers produced larger offspring that matured at larger sizes, and subsequently produced more eggs per clutch (Coakley et al, 2018;Plaistow et al, 2015). Such positive effects of age in early life often come at the cost of longevity, potentially reducing offspring lifetime fitness (Fox, Bush, & Wallin, 2003;Hercus & Hoffmann, 2000;Plaistow et al, 2015;Priest, Mackowiak, & Promislow, 2002;Zehnder, Parris, & Hunter, 2007). These effects can have important consequences on the fitness of specific genotypes and ultimately population dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…There is a clear need for more theory to explore the evolution of maternal effect senescence in offspring traits other than neonatal survival. For example, models that clarify the conditions under which the Lansing effect evolves would be an especially welcome addition to the literature, as this phenomenon is widely investigated (Comfort 1953;Butz and Hayden 1962;Klass 1977;Priest et al 2002;Zehnder et al 2007;Yilmaz et al 2008). However, as is the case for maternal effect senescence manifested as variation in neonatal survival, there exists no systematic review of the diversity of this phenomenon.…”
Section: Disentangling Maternal Age Effects 000mentioning
confidence: 99%